Milky Way chemo‐dynamics in the era of Gaia. Issue 8 (30th September 2016) - Minchev, I.; Chiappini, C.; Martig, M.
Abstract: The main goal of Galactic Archaeology is understanding the formation and evolution of the basic Galactic components. This requires sophisticated chemo‐dynamical modeling, where disc asymmetries (e.g., perturbations from the central bar, spirals arms, and infalling satellites) and non‐equilibrium processes are taken into account self‐consistently. Here we discuss the current status of Galactic chemo‐dynamical modeling and focus on a recent hybrid technique, which helps circumvent traditional problems with chemical enrichment and star formation encountered in fully self‐consistent cosmological simulations. We show that this model can account for a number of chemo‐kinematic relations in the Milky Way. In addition, we demonstrate that (1) our model matches well the observed age‐[α/Fe] and age‐[Fe/H] relations and (2) that the scatter in the age‐[Fe/H] relation cannot be simply explained by blurring (stars on apo‐ and pericenters visiting the solar vicinity) but significant radial migration (stars born elsewhere but ending up at the solar vicinity today because of a change in guiding radius) is needed. We emphasize the importance of accurate stellar ages, such as those obtained through asteroseismology by the CoRoT and Kepler missions, for breaking the degeneracy among different Galactic evolution scenarios.